Effect of coal properties on the strength of coke under simulated blast furnace conditions. (1st February 2019) - Xing, Xing; Rogers, Harold; Zulli, Paul; Hockings, Kim; Ostrovski, Oleg
Abstract: Eight cokes made from coals/blend with different properties (vitrinite mean maximum reflectance = 0.90–1.66, logarithm Gieseler maximum fluidity = 4.16–1.30) were subjected to gasification and annealing simulating the conditions within an ironmaking blast furnace (BF). The specific methodology utilised included gasification of coke with BF gas-temperature profile from 900 to 1400 °C (corresponding from the thermal reserve zone to the cohesive zone) and annealing of coke up to 2000 °C (corresponding to the raceway region). The coke microstrength and macrostrength were determined using ultra-micro indentation and tensile test to understand the effect of coal precursor properties on the strength of the resulting coke and the changes when processed under the simulated BF conditions. Under the high temperatures in the simulated BF processes, the cokes from different coals showed significant differences in their properties, even though most of them had similar Coke Reactivity Index (CRI) and Coke Strength after Reaction (CSR) values. Coke microtextures experienced significant reflectance loss and structure change upon simulated BF gasification and annealing conditions. The decreases in mean maximum reflectance and bireflectance were more severe for the coke produced from the high rank coal. The cokes made from coals with higher rank and lower Gieseler maximum fluidity exhibited greater change in their microstructure upon high temperatures. As a result, microstrength of cokes produced from these coals decreased more than that of coke made from the parent coals with a lower rank and higher Gieseler maximum fluidity; this tendency was more significant in the Reactive Maceral Derived Components (RMDC) than Inert Maceral Derived Components (IMDC) microtextural type. Degradation of macrostrength of cokes produced from coals with higher rank and lower maximum fluidity was also more severe due to the greater decrease in their microstrength.